Factors influencing warehouse construction in relation to safe operation - Cempírek, Václav; Drahotský, Ivo; Průša, Petr; Nachtigall, Petr (TANGER, spol. s r.o., 2016)
The article deals with safety in warehouses. The article focuses on work safety for drivers of handling equipment and compliance to technological procedures for loading goods onto shelves. Failure to comply with safety rules causing damage to goods and reduces the efficiency of logistics companies. Currently, safety conditions are being violated because of the employment of unskilled workers - logistics operators. In the Czech Republic a dual system of education does not prepare the appropriate personnel. Main aim of this article is to analyze safety in logistic and focus to safety in warehouses and give possible suggestion how to improve current situation in safety in Czech Republic.
Faktory ovlivňující konstrukci skladu ve vztahu k bezpečnému provozu
Keywords: warehouse; logistics; forklift; sklad; logistika; vysokozdvižný vozík